Effectiveness of Chronic Disease Management Program in Improving “CERDIK” Healthy Behavior in Patients with Hypertension in Gunungkidul, Yogyakarta - Tri Puji Pangesti; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Hypertension is the single largest contributor to the global burden of disease (GBD). The Chronic Disease Management Program (Prolanis) is a health service system and a proactive approach implemented in an integrated manner. This study aimed to determine the effectiveness of Prolanis on the